Obvezni izvod v kartografski in slikovni zbirki Narodne in univerzitetne knjižnice - Šolar, Renata (Knjižnica, 2007)
Legal deposit has been the most important way of the acquisition of cartographic and pictorial library materials. For the period from 1948 to 1991, it represented up to 80% of the inflow, composed mostly of postcards, obituaries, posters, congratulation cards, holly cards, calendars, maps, prints and atlases. High numbers of up to 5.000 copies were noted in the 70's and 80's. A notable decrease of items received through legal deposit was noted after 1991. Total inflow was between 1.000 and 2.000 copies per year. Traditional print maps and atlases still represent the majority of contemporary cartographic legal deposit inflow along with posters, postcards and calendars of pictorial materials.
Keywords: obvezni izvod; kartografsko gradivo; slikovno gradivo; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana